High Level of the Fibrin Degradation Products at Admission Predicts Parenchymal Hematoma and Unfavorable Outcome of Ischemic Stroke After Intravenous Thrombolysis - Liu, Chang; Zhang, Yun; Niu, Lingchuan; Li, Jiani (Frontiers in Neurology, 2022)
Background and Purpose: We aim to investigate whether higher admission fibrin degradation products (FDP) levels are associated with parenchymal hematomas (PH) and unfavorable outcome after intravenous thrombolysis. Methods: Consecutive acute ischemic stroke patients treated with intravenous thrombolysis were studied. The FDP level was obtained on admission. PH was evaluated 24 hours after treatment. The unfavorable outcome was defined as a 90-day modified Rankin Scale ＞ 2. Multivariable linear stepwise regression was used to assess independent factors associated with log-transformed FDP (lgFDP). Receiver operating characteristics (ROC) curve analysis was used to determine the predictive value of FDP level for unfavorable outcome. Logistic regression was used to identify independent predictors for PH and unfavorable outcome. Mediation analyses were performed to investigate associations among FDP level, PH, and outcome. Results: A total of 181 patients were included in the final analyses (median age, 73 (63-79) years; 102 (56.4%) males; median baseline NIHSS score, 8 (5-15)). The lgFDP was independently associated with age (B = 0.011, 95%CI 0.006-0.015, P < 0.001) and baseline NIHSS score (B = 0.016, 95%CI 0.008-0.025, P < 0.001). The FDP was positively associated with PH (OR 1.034, 95% CI 1.000-1.069; P = 0.047). According to the ROC analysis, the best discriminating factor for unfavorable outcome was FDP ≥ 3.085μg/ml. The FDP ≥ 3.085μg/ml was an independent predictor of unfavorable outcome (OR 7.086, 95% CI 2.818-17.822; P ＜ 0.001). Mediation analysis revealed that the association of FDP ≥ 3.085μg/ml with unfavorable outcome was not mediated by PH (P = 0.161). Conclusions: Admission FDP levels can predict PH and unfavorable outcome in acute ischemic stroke patients after IVT. PH does not mediate the effect of the FDP level on the outcome.